Social Innovation Role in Creating a Methodological Framework Adapted to Reality - Ep Chedli, Mariem Kchaich; Floricel, Teodora Bianca; Mihoreanu, Larisa (Journal of Economic Development, Environment and People, 2014)
Innovation remains a complex concept that can’t be analysed and researched by ignoring the definition and influences of all aspects and interactions which were identified in the innovation cycle. Consequently the paper initiate the development of a modern methodological framework to be applied for analysing business social innovations in its continuity to be used by companies to adapt their activities to the current market demands. These innovations are intended for running innovative company, with employees ready for new ideas. The research development has taken into analyse several approaches: the concept of social innovation, the manner of which social innovation can be analysed, focusing on methodological aspects and the third part presents the conclusions. Given the present economic crises effects, its societal and social consequences in a reduced interest for applied social innovation, people tend to choose not making changes in their life and work despite new and innovative ideas; this can be taken as an approach for to avoiding risks and activity disruptions. As results our expectations merge within the idea that a complex society requires complex answers at all problems and personalised applications of any new theory or idea. Therefore the purpose of the paper is to propose concrete ideas of social innovation that can be easily put into practice.